Arthroscopy of the Inferior Compartment of the Temporomandibular Joint: A New Perspective - González-García, Raúl (J Maxillofac Oral Surg, 2017)
OBJECTIVE: Arthroscopy of the temporomandibular joint (TMJ) has become a well-standardized non-invasive procedure for the treatment of TMJ internal derangement (ID). Since the last 1980s, no clinical application for arthroscopy of the inferior compartment has been established because of the intrinsic difficulty of the technique and the believing of the absence of clinical relevance for treatment of ID. METHODS: We report on a particular case in which arthroscopy of the inferior joint compartment together with the examination of the upper joint space was performed in a patient with ID of the TMJ. A 1.9 mm scope was used, while the technique for entering the inferior compartment is presented. RESULTS: The presence of intense synovitis, fibrous adhesion, and pseudowall were observed in the inferior joint compartment, thus leading to the hypothesis of the more than likely influence of the status of the synovial lining within this space in the persistence of symptoms in recalcitrant patients with ID. CONCLUSION: We believe that this new insight could lead surgeons to a more complete use of this non-invasive procedure for the treatment of this entity. LEVEL OF EVIDENCE: 4/5. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12663-017-1023-x) contains supplementary material, which is available to authorized users.